KEPRIBADIAN TOKOH LOUISE DALAM CHANSON DOUCE - Vina Oktaviana Tjunaldy; Hasbullah Hasbullah; Irianti Bandu (Bajang Institute, 2022)
The subject of this research is Chanson Douce, a novel by Leila Slimani, published by Gallimard in 2016. The aim of this research is to describe the character of Louise, to explain the interactions of Louise with the other characters represented in the novel Chanson Douce, and analyse Louise`s personality. The theories used are character and characterization theory from the point view of literary psychology, the relation between social background and characterizations, and personality theory by Karen Horney. Louise is a neurotic sufferer who doesnËˆt have a happy experience life also environment factor that canËˆt fulfil her neurotic needs anymore that becomes the top of LouiseËˆs intrapsychic conflict in self hatred form. The conclusions of this research are the environment and the experiences of life have a big impact on the formation of an individualËˆs personality and the external appearance is not a guarantee that a person is in good mentally or psychologically health.